Elevational Pattern of Orchid Rarity and Endemism in Mt. Kalatungan, Mindanao Island, Philippines - Betanio, Jessa Marie Garsuta; Buenavista, Dave Paladin (Journal of Tropical Life Science, 2018)
Despite being the Philippines most threatened group of plants, ecological studies on the orchid flora remains to be scanty and poorly studied which become an impediment to their conservation. This study aimed to identify the forest zones and species of conservation priority with an emphasis on the rare and endemic or-chid species.Â A field investigation was carried out using a line transect and plot-sampling methods established along the elevational zones of Mt. Kalatungan Range National Park. Results showed the presence of 44 orchid species belonging to 28 genera, 39 (91%) species of orchids are Philippine endemic with eight new records. The elevational pattern of species followed a double humped-shaped pattern at 1,320-1,395 m and 1,886 â€“ 1,965 m above sea levels (masl). Based on rarity index, 35 (83%) species are very rare, three (7%) are sparse, three (7%) common and one (3%) is common. The density of endemism was recorded to increase as eleva-tion increases which peaked at 1,886 â€“ 1,965 masl but declines at 2,000 masl Findings of the study suggest that the elevational pattern of orchid species follows a humped-shaped pattern wherein species richness is highest in the middle of the elevation gradient.